2023
DOI: 10.3390/ijerph20021311
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Removal of Heavy Metals from Contaminated Sunflower Straw by an Acid-Assisted Hydrothermal Process

Abstract: The removal of heavy metals is crucial to the utilization of contaminated biomass resources. In this study, we report an efficient process of hydrothermal conversion (HTC) of sunflower straw (Helianthus annuus L.) to remove heavy metals. The effect of different HTC temperatures and concentrations of HCl additives on heavy metal removal efficiency was investigated. The results revealed that increasing the temperature or concentration of HCl promoted the transfer of heavy metals from hydrochar to liquid products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 46 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Nonetheless , Fei et al (2019) and Song et al (2023) demonstrated the reduction of heavy metal retention in hydrochar by removing the elements from the hydrochar to the liquid products. In a study conducted by Song et al (2023), it was observed that the hydrothermal carbonization of sunflower straws at 200 °C, coupled with a 2% hydrochloric acid pre-treatment, resulted in significant removal of zinc, cadmium, copper, and lead. The maximum removal percentages for these heavy metals from the hydrochar to the liquid product were reported as 99, 99, 94, and 87%, respectively.…”
Section: Future Research Directions For Phosphorusloaded Biocharmentioning
confidence: 99%
“…Nonetheless , Fei et al (2019) and Song et al (2023) demonstrated the reduction of heavy metal retention in hydrochar by removing the elements from the hydrochar to the liquid products. In a study conducted by Song et al (2023), it was observed that the hydrothermal carbonization of sunflower straws at 200 °C, coupled with a 2% hydrochloric acid pre-treatment, resulted in significant removal of zinc, cadmium, copper, and lead. The maximum removal percentages for these heavy metals from the hydrochar to the liquid product were reported as 99, 99, 94, and 87%, respectively.…”
Section: Future Research Directions For Phosphorusloaded Biocharmentioning
confidence: 99%